O RenovaBR e a renovação da política brasileira : formação política, discursos e perspectivas - Santos Filho, Genivaldo Gonçalves dos (2021)
This research is centered on the policy experimentation process of Sergipe people who were conclusive of the RenovaBR formation processes in the periods 2018 to 2020. The RenovaBR comprises a type of organization analogous to social movements, which acts according to an organizational structure and a set of initially similar strategies, so that this condition of analogy allowed me to investigate it based on studies on social movements and their implications in the field of politics, which, despite being relatively recent, were established in a period of significant sociocultural transformations in the world, particularly with regard to the forms of action and insertion in the field of politics, as well as the struggles arising from the dynamics raised by the intersection between social movements as representatives of civil society and the State as regulator of institutional spaces in which politics is developed. The interest in undertaking this research arose from the curiosity to understand how RenovaBR is inserted in this context of the dynamics of insertion and performance in the field of Brazilian politics, and it is necessary to situate it from the time frame of its creation in relation to its trajectory and literature that contemplates its forms of operation and its consequences, that is, the end of the 20th century (when the Brazilian State was redemocratized) and the first two decades of the 21st century (when this democracy was reestablished). In this way, I used the ethnographic perspective to propose the examination of the ways in which RenovaBR operates in relation to the context of the crisis of representativeness of the Brazilian political system, as well as its proposal to insert and act in Brazilian institutional politics in the name of a renewal of this policy, which permeates the logic of restructuring the language of this field from the use of digital social networks as action tools for recruitment, dissemination and training of these new political leaders to the consolidation of a project in Brazil defended by RenovaBR.